Implementation of Attributive and Delegative Authority of Sub District Head in the Local Government Procedures - Imam Wicaksono; Amalia Diamantina (Universitas Ahmad Dahlan, 2019)
Introduction to The Problem: The authority of Sub District Head in Gringsing sub district came from attributive sources through Law No. 23 of 2014 concerning Local Government and delegative sources through the Regulation of Batang No. 77 of 2015. After the regulation was enacted, the authority of Sub District Head both attributively and delegatively changed, its position as a regional leader also changed.Purpose/Objective Study: The purpose is to know the implementation of attributive and delegative Sub District Head’s authority by looking at the regulations both in the laws and regulations below it.Design/Methodology/Approach: This research is an empirical juridical legal research. In empirical legal research, identification and law are conceptualized as a real social institution. The focus of this research is limited to Gringsing District, Batang Regency, Central Java.Findings: Referring to the attributive authority of Sub District Head after Law No. 23 of 2014 concerning Local Government, in general, there is no meaningful authority inside. Instead of being regulated in the provisions of the legislation, the material is more on the delegation of authority from the Regent (Bupati), which in this case is enough by delegative way. Moreover, after Law No. 6 of 2014 concerning Villages where the position of the village is increasingly strengthened administratively and politically are increasingly independent thus the Sub District Head’s authority is more narrowed.Paper Type: Research Article